Where do gambling problems fit in the structure of psychopathology during emerging adulthood?. Issue 1 (2nd January 2020) - King, Serena M.; Saunders, Gretchen R. B.; Elkins, Irene J.; Winters, Ken C.; Iacono, William G.; McGue, Matt
ABSTRACT: Research suggests major mental disorders co-occur at higher than chance levels. In adult samples, a two factor structure emerges when modeling the higher order structure of psychopathology. Specifically, disorders tend to co-aggregate into two dimensions: Internalizing (depression and anxiety) and Externalizing (acting out, impulsive, and addictive) disorders. Despite this large body of evidence, few studies have integrated problem gambling into this overall model. We used confirmatory factor analysis to model how the symptom count of gambling fits into the structure of psychopathology in a large, community based young adult twin sample of men and women (age 24; N = 1329). Twins were assessed via in-person, structured diagnostic interviews on disorders including: Major Depression, Phobias, Post-Traumatic Stress Disorder and Anxiety Disorders (internalizing) and Substance Use Disorders, Gambling Problems (self-report), and Antisocial Behaviors (externalizing). The data were fit to a two-factor structure, with gambling symptoms loading most highly on externalizing, rather than internalizing. The problem gambling loadings did not differ by sex. Implications of these findings suggest that during emerging adulthood gambling problems are best classified and conceptualized in the realm of externalizing disorders for both males and females. Results also suggest prevention and intervention efforts be aimed at young adults who exhibit commonly co-occurring psychopathology.